INTERNALISASI NILAI-NILAI MODERASI BERAGAMA DALAM PEMBENTUKAN KEPRIBADIAN PESERTA DIDIK DI SMK NEGERI 69 JAKARTA - Mukmin, Nurul; Sastradiharja, EE. Junaedi; susanto, Susanto; Sarnoto, Ahmad Zain (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2024)
This research aims to determine the impact of internalizing the values of religious moderation on the attitudes, thought patterns and behavior of students at SMK Negeri 69 Jakarta. This is based on the achievements of years of tolerance that internalization efforts are very important for middle level teenagers, they are often unsure and easily influenced by wrong religious ideologies. This research uses a narrative qualitative approach, with the research object being students in grades X-XII for the 2023/2024 academic year. This research data comes from observation, direct interviews in the field, and through documentation study techniques. The findings of this research show 1. Internalization of moderation values through the role of the curriculum; 2. Hidden curriculum by integrating teaching and learning and extracurricular content; and 3. Instilling moderation values through the 5S program (Senyum, Sapa, Salam, Sopan, dan Santun). Students at SMK Negeri 69 Jakarta initially did not have an understanding of the values of religious moderation and low personality, such as attitudes, thought patterns and behavior that were indifferent, selfish and ignorant. However, they have excellent potential to be developed through various educational processes in achieving national education goals in realizing the golden generation of 2045 as role models for moderate students.